MILCOM 2021 - 2021 IEEE Military Communications Conference (MILCOM) 2021
DOI: 10.1109/milcom52596.2021.9652948
|View full text |Cite
|
Sign up to set email alerts
|

DeepCQ+: Robust and Scalable Routing with Multi-Agent Deep Reinforcement Learning for Highly Dynamic Networks

Abstract: Opportunistic routing relies on the broadcast capability of wireless networks. It brings higher reliability and robustness in highly dynamic and/or severe environments such as mobile or vehicular ad-hoc networks (MANETs/VANETs). To reduce the cost of broadcast, multicast routing schemes use the connected dominating set (CDS) or multi-point relaying (MPR) set to decrease the network overhead and hence, their selection algorithms are critical. Common MPR selection algorithms are heuristic, rely on coordination b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…This paper presents a QoS-assured intelligent routing system for WMNs with high traffic loads that use reinforcement learning to improve performance [27]. As per Saeed Kaviani et al, DeepCQ+ routing, which combines emerging multiagent deep reinforcement learning (MADRL) in a novel way, achieves persistently higher performance across a wide range of MANET architectures while training only on a limited range of network parameters and conditions [28]. In a fully decentralized environment, Xinyu You et al developed a unique packet routing framework based on multi-agent deep reinforcement learning.…”
Section: Overview Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper presents a QoS-assured intelligent routing system for WMNs with high traffic loads that use reinforcement learning to improve performance [27]. As per Saeed Kaviani et al, DeepCQ+ routing, which combines emerging multiagent deep reinforcement learning (MADRL) in a novel way, achieves persistently higher performance across a wide range of MANET architectures while training only on a limited range of network parameters and conditions [28]. In a fully decentralized environment, Xinyu You et al developed a unique packet routing framework based on multi-agent deep reinforcement learning.…”
Section: Overview Of Related Workmentioning
confidence: 99%
“…An optimal Q-table contains values that allow the AI agent to take the best action in any possible State, thus providing the agent with the potential path to the highest reward. The Qtable, therefore, represents the AI agent's policy for acting in the current environment [28]. In Q-learning, the Temporal Differences' TD' provide a method of calculating how much the Q-value for the action taken in the previous State should be changed based on what an AI agent has learned about the Q-values for the current State's actions.…”
Section: F Working Of Q-learningmentioning
confidence: 99%
“…From node to network level, security in MANETs is important 6 . Owing to the dynamic nature of MANETs, there needs to be an acceptable level of trust 7,8 . Due to the dynamic nature and characteristics of MANETs, ​​security on the MANET is more challenge than in typical network environments with a central controller 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Owing to the dynamic nature of MANETs, there needs to be an acceptable level of trust. 7,8 Due to the dynamic nature and characteristics of MANETs, security on the MANET is more challenge…”
mentioning
confidence: 99%
“…Researchers have applied DRL algorithms for various problems in mobile ad-hoc networks (MANETs), e.g., for minimizing average or worst-case end-to-end delay in routing problems [2], [3] and routing path optimization [4]. In [5], it is shown that the DRL-based DeepCQ+ algorithm outperforms the state-of-the-art robust routing for dynamic networks (R2DN) [6]. In this context, robust routing relies on the routing of the unicast data flows with the availability of simplified multicast forwarding (SMF) (as simplified data flooding and relaying) among routing peers [7].…”
Section: Introductionmentioning
confidence: 99%